Audacity Software Analysis In Analyzing The Frequency And Character Of The Sound Spectrum - Aisha Azalia; Desi Ramadhanti; Hestiana Hestiana; Heru Kuswanto (Postgraduate, University of Mataram, 2022)
In the process of learning physics, experiments are needed that can help someone in gaining a deeper understanding of learning physics concepts and using technology in the learning process, especially learning sound waves. In this study, the aim is to be able to analyze the sound frequency with the help of Audacity software. Subjects used are 5 different cat sounds. The implementation of this research uses several tools such as a microphone, Audacity software on a laptop, and 5 cat sounds. This experiment was carried out by bringing the micro hope closer to the cat with 5 cm so that the sound was captured by the microphone which would later be transferred to the laptop and read by the audacity software. Furthermore, the data recorded in audacity were analyzed. From the results of the study, it can be said that a tool that can be used in practicum and can read and capture sound waves is effectively used in analyzing sound frequency, spectrum in the application of sound learning so that it can be used as one of the learning media in practicum on sound wave material at Junior high school.